Tourism recovery strategies during major crises: The role of proactivity. (September 2021) - Raki, Amir; Nayer, Daud; Nazifi, Amin; Alexander, Matthew; Seyfi, Siamak
Highlights: Tourism failures during a crisis can threaten consumer wellbeing. Proactive recovery strategies can improve various dimensions of consumer wellbeing. Proactive recovery strategies can enhance firm profitability and reduce employee attrition.